America first? Uma análise do lugar da OTAN na política externa dos Estados Unidos no governo Donald Trump sob a ótica do modelo proposto por Charles Hermann - Lima Filho, Gilberto de Almeida (2023)
The present master’s thesis deals with the foreign policy of the United States of America (USA) and an international organization with a security bias, led by this actor, the North Atlantic Treaty Organization (NATO). The importance of analyzing the foreign policy of the Donald J. Trump administration takes place in the conjuncture of the development of this policy, as the former president put into perspective the leadership of the United States in some international organizations, among them NATO. In this regard, the research question is: what is NATO's place in US foreign policy? In this way, the master’s thesis will analyze the US foreign policy actions regarding the Alliance during the Trump administration, with the aim of understanding the influence of the Americans and the reason for a possible redirection in the American agenda for this organization. The methodological path that will be used will be based on the model proposed by Hermann (1990), with the objective of evaluating the existence of any change in relation to the US foreign policy agenda for NATO, when compared to the pattern developed after the Cold War, situation in which there will be a degree of framing of the change, within the possibilities addressed by Hermann. For the purpose of analyzing the framework of change, statistical data provided by NATO were used, together with the theoretical framework constructed with regard to the analysis of Trump's foreign policy.